Visioner Leadership In Education And Training Organizational Capacity Development In The Era Of Covid 19 Disruption And Industry 4.0 - Gian Yekti Widodo (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The aims of the study is to reveal visionary leadership in developing organizational capacity in the era of disruption to the covid-19 and industry 4.0. This research used a qualitative descriptive approach with a case study at the Human Resources Development Center of Manpower (PPSDM) in Jakarta, Indonesia. Informants were structural officials, coordinators and sub-coordinators, widyaiswara, staff and training participants whose data were taken through interviews, observations and other documents such as program documents, implementation to evaluation as secondary data. Visionary leadership plays an important role in developing organizational capacity in times of Volatile, Uncertain, Complex and Ambiguous. There are several competency domains that must be implemented by a tough leader today, namely business, leadership, interpersonal and intrapersonal domains.